Religious Graffiti in the Western Mediterranean (18th Century): An Approach from the Notion of Iconic Presence - Agües Escolano, Irene (Eikón / Imago, 2026)
This article offers a theoretical approach to the study of iconic graffiti with religious themes through a selection of Mediterranean cases from the 18th century. In this context, the graffiti are interpreted as graphic expressions of popular religiosity. The conceptual framework is articulated from the notion of iconic presence formulated by Hans Belting, complemented by the idea of image-matter by José Luis Brea and by the conception of graffiti as acts of material devotion proposed by Ann Marie Yasin. The study examines the dynamic relationship between subject, image, and object of worship